Evaluation of polyhydroxyalkanoate (PHAs) production with a bacterial isolate using cassava flour hydrolysates as an alternative substrate (2019)
ABSTRACT: In the production of polyhydroxyalkanoates (PHAs), the costs of the process are mainly associated with the carbon source and most production studies are carried out with commercial strains. In this study, PHAs production was evaluated using SB-34, a wild-type strain, in comparison with Ralstonia eutropha H16, a referenced strain growing in cassava flour hydrolysates, as an alternative carbon source. SB-34 reached a maximum biomass of 5,49 ± 0,21 g / L, and a PHAs production of 3,23 ± 0,21 g / L, exceeding the maximum values obtained by R. eutropha H16 (3,8 ± 0,45 g / L and 2,42 ± 0,23 g / L, respectively). Analyses with FTIR indicated that the polymer obtained with SB-34 is a P(3-HB) polyhydroxybutyrate. A molecular analysis identified SB-34 as Burkholderia sp. with 96 % of similarity.